Student’s Perception About Entrepreneurship Containing the Value of Pancasila as a Basic Construction of Entrepreneurship’s Subject in Unesa - Susanti, Susanti; Handayaningrum, Warih; Subroto, Waspodo Tjipto (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to (1) describe students' perception of entrepreneurial values, (2) analyze Pancasila values that need to be developed in entrepreneurial learning and (3) describe the construction of entrepreneurial learning to produce Pancasila entrepreneurs. The method in this study was qualitative research. The sample in this study was Universitas Negeri Surabaya students who had taken Entrepreneurship courses, as many as 48 students. Data collection techniques using observation and documentation in the form of questionnaires and photos of activities. Data analysis techniques using reduction, presentation and conclusion. The conclusions of this study are (1) the perception of students has a positive category on the benefits of entrepreneurship, mental attitude and their views on Pancasila entrepreneurs, (2) the Pancasila values developed are the values in sila 1 and value 2 which are directly related to the substance of entrepreneurs. Meanwhile, other precepts also need to be a supporter and perfect attitude as an Indonesian and (3) the construction of the entrepreneurship course offered aims to complete the Entrepreneurship course module formulated by the 2016 Entrepreneurship Team, which is through tasks that are given mental attitude processes, personal formation and implementation of the Pancasila values.